2018
DOI: 10.1105/tpc.18.00401
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Division Planes of Three-Dimensional Cells by Soap-Film Minimization

Abstract: One key aspect of cell division in multicellular organisms is the orientation of the division plane. Proper division plane establishment contributes to normal plant body organization. To determine the importance of cell geometry in division plane orientation, we designed a three-dimensional probabilistic mathematical model to directly test the century-old hypothesis that cell divisions mimic soap-film minima. According to this hypothesis, daughter cells have equal volume and the division plane occurs where the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Previous measurements of PPB placement were obtained from 2D micrographs, which might not accurately reflect the position of the PPB in 3D, particularly in cells with irregular shapes. To overcome this shortcoming, we used our recently developed mathematical modeling approach to accurately predict 3D division planes ( Martinez et al, 2018 ). This model generates soap-film minima from real, 3D cell shapes and allows us to compare purely geometric predictions to in vivo cell division sites ( Martinez et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous measurements of PPB placement were obtained from 2D micrographs, which might not accurately reflect the position of the PPB in 3D, particularly in cells with irregular shapes. To overcome this shortcoming, we used our recently developed mathematical modeling approach to accurately predict 3D division planes ( Martinez et al, 2018 ). This model generates soap-film minima from real, 3D cell shapes and allows us to compare purely geometric predictions to in vivo cell division sites ( Martinez et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the gradient descent function in Surface Evolver was used to generate soap-film minima that divided the volume into two equal halves. These soap-film minima are division planes predictions (Martinez et al, 2018;Brakke, 1992). The predicted division planes were then compared with the in vivo PPB location (Fig.…”
Section: His-tan1 Mediates Lateral and End-on Microtubule Interactionmentioning
confidence: 99%
“…While the revised version of the present paper was under review, Martinez et al [47] published a 3D model of symmetric cell divisions and Chakrabortty et al [48] reported how they attempted to predict the global orientation of division planes in the embryo based on the organization of cortical microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Another structure aligning with tension is the PPB whose orientation often follows the main orientation of cortical microtubules in interphase. PPB position is accurately predicted by the soap-film area minimization model run on real 3D segmented cell templates, in turn, the PPB position predicts the position of the future division plane [ 13 , 28 ]. However, PPB is not present in all plant species [ 29 ] and its function has recently been re-evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Divisions parallel to the longest axis of the cell, referred to as longitudinal divisions hereafter, are frequent during leaf development in maize [ 48 ]. However, they tend to occur in nearly isotropic cells, making the selected path not so distant from the shortest path [ 28 ]. Besides this situation that can be interpreted as an extreme case of the Besson and Dumais rule, some deviations from the shortest path cannot be explained by cell geometry-based rules alone.…”
Section: Introductionmentioning
confidence: 99%